Progesterone profile, ovarian response and embryo recovery in prostaglandin F2 alpha and syncro-mate-B in combination with folltropin treated crossbred cows* - AROSH, A. JOE; SAKHILA, K; DEVANATHAN, T G; KATHIRESAN, D (The Indian Journal of Animal Sciences, 2013)
Crossbred cows (16) were divided into PGF2 a and SMB groups. Prostaglandin F2 alpha and syncro-mate-B were used to induce oestrus and superovulated with folltropin. The embryos wen: collected non significantly. The number of ovulations, embryo recovery and transferable embryos were significantly higher in PGF2 a group and the number of nontransferable embryos were significantly higher in 5MB group. The progesterone concentration on the day of iniliation of super ovulatory treatment, on the day of PGF2 a administration and on the day of embryo collection was significantly higher in PGF2 a. group, while the progesterone concentration on the day ofsuperoestrus and on day 3 post superoestrus did not showÂ  my significant difference. The progesterone concentration registered an increasing trend between FSH injection in POF2 a. group and not in 5MB group. In both the groups the progesterone concentration on the clay of sLiperoestrus, on day 3 post sLiperoestrus and on the day of embryo collection is significantly positively correlated with number or ovulations, embryo recovery and transferable embryos. But the progesterone cf'oIcentration on the day of initiation of supcrovulatory treatment and on the day of PGF2 a. administration (during super ovulation) is positively correlated with number of ovulations, embryo lecovery and transferable embryos only in PGF2 alpha group not in SMB group. Therefore, the progesterone concentration on the day of initiation of superovulatory treatment and on the day of POF2 a adminisfration (during super ovulation) can be used as tool only in PGF2 alpha group and cannot be used as tool in SMB group to predict the ovarian response, embryo recovery and quality of embryos in crossbred cows.